Teknologi Three-Parent Baby dan Implikasinya terhadap Nasab Perspektif Sadd adz-Dzari’ah - Nida Rafiqa Izzati; N. Nurnazli; Abdul Qodir Zaelani; M. Natsir Asnawi; Rezkia Zahara Lubis (Jurnal Interpretasi Hukum, 2025)
The Three-Parent Baby Technology (TPBT) is a medical innovation aimed at preventing the hereditary transmission of mitochondrial disorders by combining genetic material from two women and one man. While offering a health solution, this technology raises significant issues in Islamic law, particularly regarding lineage clarity (nasab). This study addresses three main focuses: first, the concept and development of TPBT in medical science; second, the principle of sadd adz-dzari’ah as a method of legal determination in Islam; and third, the analysis of TPBT from the sadd adz-dzari’ah perspective and its implications for lineage in Islamic family law. Employing a qualitative approach through library research, this study draws from primary and secondary sources in Islamic legal discourse. The findings indicate that while TPBT is clinically effective, it remains uncertain in terms of long-term safety. In Islamic law, sadd adz-dzari’ah functions as a legal method that prevents harm by closing avenues leading to potential damage (mafsadat). From this perspective, TPBT risks obscuring lineage, violating Sharia principles of reproduction, posing long-term health risks (for both the woman undergoing the procedure and the resulting child), exploiting women, enabling genetic engineering abuse, and conflicting with the concept of qadha and qadar. Based on its inherent potential for harm, TPBT falls into the category of acts that are intrinsically prohibited due to their destructive nature. Scholars agree that such actions must be prevented. Therefore, through the lens of sadd adz-dzari’ah, TPBT is assessed as causing more harm than benefit and is deemed inappropriate for implementation in Islamic family law.